Remote general meeting of shareholders: are the shareholders‘ rights respected? - Janušauskaitė, Milda Aušrinė; Jucytė, Gabija (Vilnius University Open Series, 2023)
A lockdown due to Covid-19 virus, which restricted the right to gather, was announced by the Government of the Republic of Lithuania in March 2020. The lockdown severely affected the activity of public and private limited liability companies’ body – the general meeting of shareholders, i. e. the manager’s had to find alternative ways to organize the general meeting of shareholders that would not pose a risk to the shareholders’ health due to the pandemic situation.In this article we will discuss the problems that arise from moving the general meeting of shareholders to electronic space, whether the rights of the shareholders are respected in such situation and how the general meeting of shareholders was organized in 2020 and 2021 when taking into account the recommendations adopted by Government resolutions.
Keywords: remote general meeting of shareholders; shareholder; shareholder’s rights; electronic means of communication; voting in advance